Microglial Nrf2-mediated lipid and iron metabolism reprogramming promotes remyelination during white matter ischemia - Hang Zhang; Sheng Yang; Yi-Lin Lu; Luo-Qi Zhou; Ming-Hao Dong; Yun-Hui Chu; Xiao-Wei Pang; Lian Chen; Lu-Lu Xu; Lu-Yang Zhang; Li-Fang Zhu; Ting Xu; et al. (Redox Biology)
Background: Oxidative stress and microglial activation are critical pathomechanisms in ischemic white matter injury. Microglia, as resident immune cells in the brain, are the main cells undergoing oxidative stress response. However, the role and molecular mechanism of oxidative stress in microglia have not been clearly elucidated during white matter ischemia. Methods: Extensive histological analysis of the corpus callosum was performed in BCAS mice at different time points to assess white matter injury, oxidative stress and microglial activation. Flow cytometric sorting and transcriptomic sequencing were combined to explore the underlying mechanisms regulating microglial oxidative stress and functional phenotypes. The expression of critical molecule in microglia was regulated using Cx3cr1CreER mice and clinical-stage drugs to assess its effect on white matter injury and cognitive function. Results: Our study identified nuclear factor erythroid-2 related factor 2 (Nrf2) as a key transcription factor regulating oxidative stress and functional phenotype in microglia. Interestingly, we found that the sustained decrease in transiently upregulated expression of Nrf2 following chronic cerebral hypoperfusion resulted in abnormal microglial activation and white matter injury. In addition, high loads of myelin debris promoted lipid peroxidation and ferroptosis in microglia with diminished antioxidant function. Microglia with pharmacologically or genetically stimulated Nrf2 expression exhibited enhanced resistance to ferroptosis and pro-regenerative properties to myelination due to lipid and iron metabolism reprogramming. Conclusion: Weakened Nrf2-mediated antioxidant responses in microglia induced metabolic disturbances and ferroptosis during chronic cerebral hypoperfusion. Targeted enhancement of Nrf2 expression in microglia may be a potential therapeutic strategy for ischemic white matter injury.